Hubungan Penghasilan Orang Tua dan Dorongan Orang Tua Terhadap Pernikahan Dini - Ayudita Ayudita (Jurnal Anestesi, 2023)
Early marriage, defined as marriage before the age of 18, is regulated by Indonesian Law No. 23 of 2002 on Child Protection. This study aims to assess the relationship between parental income and family support with early marriage among adolescent girls. Data were collected from 359 respondents and analyzed using Chi-Square tests with a 95% confidence level. The analysis revealed no significant relationship between parental income (p = 0.096) and parental encouragement (p = 0.601) with early marriage. These findings contradict previous studies linking low income and parental encouragement to early marriage. The study suggests further research to explore additional factors that may contribute to early marriage. Moreover, it is crucial to raise public awareness about the impacts of early marriage and provide better support for adolescents in planning their futures. Intervention programs should consider the social and cultural factors that may influence early marriage decisions.